2015
DOI: 10.1089/zeb.2014.0972
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gnotobiotic Zebrafish to StudyVibrio anguillarumPathogenicity

Abstract: We evaluated the use of the gnotobiotic zebrafish system to study the effects of bacterial infection, and analyzed expression of genes involved in zebrafish innate immunity. Using a GFP-labeled strain of Vibrio anguillarum, we fluorescently monitored colonization of the zebrafish intestinal tract and used gene expression analysis to compare changes in genes involved in innate immunity between nongnotobiotic and gnotobiotic larvae. The experiments performed with the gnotobiotic zebrafish reveal new insights int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 47 publications
4
22
1
Order By: Relevance
“…Vibrio anguillarum is a halophilic, Gram-negative bacterium and the causative agent of haemorrhagic septicaemia (vibriosis) which can affect several fish species including salt and freshwater fish ( Toranzo et al, 2005 ; Frans et al, 2011 ) and can lead to important economic losses. In this study, we observed that the gastrointestinal tract and gills represented the principal entryways of V. anguillarum , as previously described in rainbow trout ( Spanggaard et al, 2000 ) and zebrafish ( O’Toole et al, 2004 ; Oyarbide et al, 2015 ). V. anguillarum counts in recently dead larvae were statistically higher than in survival larvae suggesting that the concentration of the pathogen in larvae could be related to the progression of the disease.…”
Section: Discussionsupporting
confidence: 80%
“…Vibrio anguillarum is a halophilic, Gram-negative bacterium and the causative agent of haemorrhagic septicaemia (vibriosis) which can affect several fish species including salt and freshwater fish ( Toranzo et al, 2005 ; Frans et al, 2011 ) and can lead to important economic losses. In this study, we observed that the gastrointestinal tract and gills represented the principal entryways of V. anguillarum , as previously described in rainbow trout ( Spanggaard et al, 2000 ) and zebrafish ( O’Toole et al, 2004 ; Oyarbide et al, 2015 ). V. anguillarum counts in recently dead larvae were statistically higher than in survival larvae suggesting that the concentration of the pathogen in larvae could be related to the progression of the disease.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, the gene NFKB involved in cellular responses to stimuli such as stress, cytokines, free radicals, ultraviolet irradiation, oxidized LDL and bacterial or viral antigens showed up regulation with 1.38 fold by which may be due to the generation of stress. But in case of all other genes a sign of down regulations were observed including IL1B a marker of inflammation in zebrafish [49] resulted in response to stress. These changes in up and down regulation in response to AgNPs exposed liver tissues resulted in various kinds of stressors.…”
Section: Resultsmentioning
confidence: 99%
“…Production of germ-free zebra sh was performed as previously described (Oyarbide, Iturria, Rainieri & Pardo, 2015). During experimentation fish were maintained at an average density of 1.3 animals per mL in sterile petri dishes housed in an air incubator at 27 °C on a 14 h light cycle.…”
Section: Animal Husbandrymentioning
confidence: 99%
“…These difficulties can be overcome using gnotobiotic models in which the microbiota is either known or absent (Pham, Kanther, Semova & Rawls, 2008). Thus, we have previously used gnotobiotic zebrafish larvae for evaluation of potentially probiotic LAB isolated from food (Russo et al, 2015), as well as for analysis of the mechanism of infection of opportunistic pathogens (Oyarbide, Iturria, Rainieri & Pardo, 2015). Consequently, in addition to in vitro evaluation of the two dextran-producing LAB, the influence of the presence of the HoPS on the activity of Lb.…”
Section: Introductionmentioning
confidence: 99%